STUDENTS' INTEREST AND MOTIVATION SURVEY ON BASKETBALL EXTRACURRICULAR ACTIVITIES AT SMP NEGERI 5 INDRALAYA UTARA - Imam Rafii'u Darajat; Hartati Hartati; Silvi Aryanti (Universitas Negeri Medan, 2022)
This study aims to determine the interest and motivation of students towards basketball extracurricular activities at SMP Negeri 5 Indralaya Utara District. This research method is a descriptive quantitative oneshot case study. The subjects in this study used a total sampling technique with 47 students taking basketball extracurricular activities. Collecting data in this study using a questionnaire that was distributed directly. Data analysis in this study used descriptive statistics of percentages in the form of a frequency table. Based on the research results obtained regarding the interest and motivation of students towards extracurricular activities of basketball at SMP Negeri 5 Indralaya Utara District with a percentage of 49.9% included in the sufficient category. The findings of this study that the interest and motivation of students in basketball extracurricular is sufficient because this basketball extracurricular is still relatively new at SMP Negeri 5 Indralaya Utara and requires adaptation for students because the initial response of students is good so extracurricular can run as it should. The implication of the results of this study is that students' interest and motivation in extracurricular activities can be increased again by improving the training program that is designed to be more attractive, the discipline of trainers and students in order to achieve the desired goals and improve extracurricular and school achievement.